Daniel's gift ebook - Freethy, Barbara (Barbara Freethy, 2011)
Fans of Debbie Macomber, Susan Wiggs, Kristin Hannah and Robyn Carr will enjoy this emotional novel of romantic women's fiction featuring love and family from #1 New York Times Bestseller Barbara Freethy. A perfect choice for your bookclub! WINNER OF RITA Award for Best Contemporary Romance - Romance Writers of America This is a full length novel of approximately 100,000 words. From the back cover: Reckless Youth ... In her impetuous summer of love, Jenny St. Claire found Luke Sheridan - her dashing knight in intern's scrubs. But a fast-track future and rigid, ambitious parents drove passion out of Luke's life. And the summer ended, leaving Jenny with a broken heart... and a beautiful son, Danny, to help mend it. From the back cover: Love Reclaimed ... Years later it is tragedy that reunites them - the father whom a son longs to know, and the mother who has tried desperately to forget. And as Luke and Jenny struggle to ignore the pain and desire reborn in a look and a touch, only the remarkable courage of a young boy - and the help of a rather unorthodox guardian angel — can offer them the most precious gift of all: a second chance at the love of a lifetime.